1970
DOI: 10.3126/nepjoph.v3i2.5270
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery in camp patients: a study on visual outcomes

Abstract: High quality cataract surgery with a low rate of intra-operative complications and good visual outcome can be attained in camp patients operated in the base hospitals, thus justifying more similar screening camps to clear the vast cataract backlog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Even though the postoperative UCVA of both surgical techniques did not match the WHO recommended standards (8), because many post-cataract patients in developing countries do not wear or cannot afford spectacles after surgery and thus rely on their UCVA to carry out their everyday functions (9,15), it is worth stating that in the current study, UCVA at 4-6 weeks' follow-up suggested that PHACO reduced the dependency of many patients on distance spectacle correction or other interventions to correct ametropias compared to MSICS. The significantly higher total astigmatic change in the MSICS group corroborates findings reported by some studies mentioned in the literature (11,16,17). This difference in total astigmatic change between the two surgical techniques could be explained by the longer incision in MSICS.…”
Section: Discussionsupporting
confidence: 89%
“…Even though the postoperative UCVA of both surgical techniques did not match the WHO recommended standards (8), because many post-cataract patients in developing countries do not wear or cannot afford spectacles after surgery and thus rely on their UCVA to carry out their everyday functions (9,15), it is worth stating that in the current study, UCVA at 4-6 weeks' follow-up suggested that PHACO reduced the dependency of many patients on distance spectacle correction or other interventions to correct ametropias compared to MSICS. The significantly higher total astigmatic change in the MSICS group corroborates findings reported by some studies mentioned in the literature (11,16,17). This difference in total astigmatic change between the two surgical techniques could be explained by the longer incision in MSICS.…”
Section: Discussionsupporting
confidence: 89%
“…[ 20 ] found that 89.3% of patients had visual acuity between 6/6 and 6/18 after cataract surgery. [ 15 ] Our study shows that out of 315 patients who underwent cataract surgery, 10 (3.16%) patients had PCR with vitreous loss in which 5 (1.58%) were implanted with IOL but the remaining 5 (1.58%) were planned for secondary IOL due to inadequate ciliary sulcus support. Out of 10 surgeries having PCR, nine were performed by resident doctors.…”
Section: Discussionmentioning
confidence: 91%
“…Despite these factors, the outcomes between larger, recognised cataract units and cataract camps are not dissimilar with respect to visual acuity and complication rates. 19 This might be explained by the fact that the same local ophthalmic professionals that operate in larger units, or privately, may undertake charitable work in cataract camps. There is also an increasing influx of foreign ophthalmologists that are running charitable organisations and outreach programmes to contribute to the improvement of reversable causes of blindness.…”
Section: Discussionmentioning
confidence: 99%